IMPROVING STUDENT LEARNING OUTCOMES IN INTEGRATED THEMATIC LEARNING THEME 6 USING DISCOVERY LEARNING MODEL IN CLASS V ELEMENTARY SCHOOL - Indra Indra; Mai Sri Lena (Universitas Majalengka, 2023)
This research is motivated by the facts in the field that show the low learning results of students in integrated thematic learning due to teachers who have not been seen developing learning models and students' understanding of the learning material provided, resulting in students participating less in participating in learning. The purpose of this research is to describe the use of the Discovery Learning Model can improve student learning outcomes in integrated thematic learning theme 6 grade V elementary school. This study is a Classr Action Research that uses qualitative and quantitative methods. It is done in two cycles, cycle I (two sessions), cycle II (one session), and it is done in four stages: planning, doing the work, watching, and thinking about it. This study's participants were 21 fifth-grade students and teachers from SDN 24 Limo Koto, Sijunjung Regency. Cycle I's lesson plan research obtain results with an score of 83%, and cycle II saw an increase, with an score of 91.6%. In cycle II, the assessment of teacher activities increased with an score of 90%. In cycle I, the score was 71.5%. The average score for assessment of learner activities in cycle I was 69.8%, and it increased in cycle II to 86.6%. In this study, integrated thematic learning outcomes had an score of 67 percentage for cycle I and an score of 81.4% for cycle II. Integrated thematic learning in class V SDN 24 Limo Koto Sijunjung Regency using the Discovery Learning Model can improve student learning outcomes. Penelitian ini dilatarbelakangi oleh fakta di lapangan yang memperlihatkan rendahnya hasil belajar siswa pada pembelajaran tematik terpadu dikarenakan guru yang belum terlihat mengembangkan model pembelajaran dan pemahaman peserta didik terhadap materi pembelajaran yang diberikan, mengakibatkan peserta didik kurang berpartisipasi dalam mengikuti pembelajaran. Tujuan penelitiąn ini adalah untuk mendeskripsikąn penggunaan Model Pembelajaran Discovery Learning dapat meningkatkan hasil belajar siswa pada pembelajaran tematik terpadu tema 6 kelas V sekolah dasar. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang menggunakan metode kualitatif dan kuantitatif. Penelitian ini dilakukan dalam dua siklus, siklus I(Dua Pertemuan), siklus II(Satu Pertemuan) dan dilakukan dalam empat tahapan; perencanaan, pelaksanaan, pengamatan dan refleksi. Partisipan penelitian ini adalah 21 siswa dan guru kelas V dari SDN 24 Limo Koto, Kabupaten Sijunjung. Penelitian RPP siklus I memperoleh hasil dengan nilai 83%, dan siklus II mengalami peningkatan dengan nilai 91,6%. Pada siklus II, penilaian aktivitas guru mengalami peningkatan dengan nilai rata-rata 90%. Pada siklus I, nilai rata-rata sebesar 71,5%. Nilai rata-rata untuk penilaian aktivitas peserta didik pada siklus I adalah 69,8%, dan meningkat pada siklus II menjadi 86,6%. Pada penelitian ini, hasil belajar tematik terpadu siswa memiliki nilai 67 untuk siklus I dan nilai 81,4% untuk siklus II. Pembelajaran tematik terpadu di kelas V SDN 24 Limo Koto Kabupaten Sijunjung menggunakan Model Pembelajaran Discovery Learning dapat meningkatkan hasil belajar siswa.